ANTIFUNGAL AND ANTIBIOFILM ACTIVITY OF 2-BROMO-N-PHENYLCETAMIDE AGAINST CRYPTOCOCCUS NEOFORMANS - DE MELO, THAMARA RODRIGUES; CORDEIRO, LAÍSA VILAR; DA SILVA SOUZA, HELIVALDO DIÓGENES; DE ATHAYDE-FILHO, PETRÔNIO FILGUEIRAS; DE OLIVEIRA-FILHO, ABRAHÃO ALVES; FERREIRA, SÁVIO BENVINDO; OLIVERIA LIMA, EDELTRUDES DE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to evaluate the antifungal and antibiofilm of 2-bromo-N-phenylacetamide (A1Br) against Cryptococcus neoformans in vitro. Methods: The compound was characterized by infrared and 1H-nuclear magnetic resonance spectrometry data. Minimum inhibitory concentration (MIC) was determined using the plate dilution method and biofilm formation inhibition of the crystal violet assay. Results: A1Br inhibited the growth of C. neoformans with MIC of 0.25 and 0.5 μg/ml and has good antibiofilm activity MIC ×4, with ≥80% inhibition growth. Conclusions: Thus, A1Br shows potential antifungal and antibiofilm agents for the treatment of infections caused by C. neoformans, as well as the eradication of cryptococcal colonization of medical prosthetic devices.